Extracorporeal life support provision in COVID-19 patients - An international EuroELSO 2022 update survey. (May 2023) - Fleig, Marcel; Müller, Thomas; Antonini, Velia M; Riera, Jordi; Belliato, Mirko; Broman, Lars Mikael; Fowles, Jo-Anne; Belohlavek, Jan; Lorusso, Roberto; Vercaemst, Leen; Jones, Tim; Roeleveld, Peter P; et al.
Introduction: An analysis on the ECLS use for patients with respiratory or cardiac support in COVID-19 based on an international response to EuroELSO survey, aims to generate a more comprehensive understanding of ECLS role during the recent viral pandemic. Methods: EuroELSO announced the survey at the 10th annual congress in London, May 2022. The survey covered 26 multiple-choice questions. Results: The survey returned 69 questionnaires from 62 centers across 22 European countries and seven centers across five non-European countries. Most of the centers providing ECLS for COVID-19 patients had more than 30 runs for respiratory support since December 2019. In the same period, at least 31 runs in adult COVID-19 patients have been performed in 48 of 69 centers (69.6%). The reported pediatric data from 18 centers is limited to less than the patients per center. Conclusion: Majority of the COVID-19 patients received respiratory ECLS support and adult patients dominated. The indications and contraindications are broadly aligned with available guidelines. Most of the centers considered age >65 or biological age as a relative or absolute contraindication for ECLS in COVID-19. ECLS withdrawal criteria in COVID-19 are controversial because the long-term outcomes after ECLS in COVID-19 and the impact of critical illness and the impact of long-COVID are still not known.